Level Of Effectiveness of School-Based Learning Action Cell (SLAC) Program in Teaching English for English Teachers - Añonuevo, Betty (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effectiveness of the School Learning Action Cell (SLAC) Program in teaching English as perceived by secondary school English teachers in five selected public secondary schools in Cataingan, Masbate. Specifically, it examined the respondents' demographic profile, assessed the effectiveness of SLAC in terms of its objectives, intended outcomes, and sustainability, and identified measures for improving its implementation. The study was anchored on the Theory of Andragogy, Social Cognitive Theory, and the Technological Pedagogical Content Knowledge (TPACK) Framework. A descriptive research design was employed using a researcher-constructed and validated questionnaire administered to twenty-seven Junior and Senior High School English teachers through total population sampling. Data were analyzed using frequency count, percentage, and weighted mean. The findings revealed that the respondents were predominantly young, female, single, bachelor's degree holders, had limited specialized English training, and possessed five years or less of teaching experience. The objectives of the SLAC Program were perceived as extremely effective, while its intended outcomes and sustainability were rated very effective. The respondents also identified advance planning, closer supervision and monitoring by school heads, adequate scheduling, and logistical support as effective measures for improving program implementation. The study concluded that the SLAC Program is an effective school-based professional development initiative that strengthens teacher collaboration, enhances pedagogical competence, and supports continuous professional growth. It recommends sustaining and institutionalizing the program, strengthening administrative support, expanding specialized English training opportunities, and conducting similar studies in other educational settings. The study supports Sustainable Development Goal (SDG) 4 – Quality Education, SDG 8 – Decent Work and Economic Growth, and SDG 17 – Partnerships for the Goals by promoting continuous teacher professional development and collaborative learning. Its findings contribute to educational, institutional, and community sustainability by providing localized evidence to strengthen school-based professional development and improve English language instruction.
Keywords: Collaborative Learning; English Language Teaching; Professional Development; School Learning Action Cell (SLAC); Secondary School Teachers; Sustainability; Teacher Competence; Teaching Effectiveness